Distribution of histopathological types of thyroid tumors in 1999-2015 compared to 1966-1988 year period - Makazlieva, Tanja; Vaskova, Olivija; Nikolovska, Aleksandra; Velikj Stefanovska, Vesna (Archive of Oncology, 2019)
Background: The most common thyroid tumors originate from the epithelial follicular cells. Etiology involved in the development of thyroid carcinoma is multifactorial, including external influences and genetic predisposition. Aim: The objective of our study was to analyze the distribution of the histopathological types of thyroid carcinoma during 1999-2015 year period, to evaluate papillary and follicular thyroid carcinoma ratio and to compare thyroid carcinoma types with the data from prior epidemiological study referring to the period from 1966 -1988. Methods: A retrospective analysis was performed. The trend for thyroid carcinoma cases was evaluated in the time period of 50 years. Percentages of different histopathological types of thyroid carcinoma were presented and papillary and follicular thyroid carcinoma ratio was calculated for the two evaluated periods. Results: A total number of 422 thyroid carcinoma patients were diagnosed in the 1999-2015 year period vs. 323 patients in the period from 1966-1988. Analysis revealed no statistically significant difference in histopathological types of thyroid carcinoma during 1999-2015 year period, but statistically significant difference was detected between the two analyzed periods with a significant increase of papillary and follicular thyroid carcinoma ratio (from 3.1 to 7.3), and a significant reduction of anaplastic thyroid carcinomas cases in the more recent evaluated period (1999-2015). Conclusion: The analysis of the fifty-year-period in population of North Macedonia showed an increase in number of thyroid carcinoma cases, especially papillary and reduction of follicular thyroid carcinoma and anaplastic thyroid carcinomas cases. Further, genetic profiling studies could be useful in evaluating possible mechanisms behind this shift in histopathology of the thyroid carcinomas.
Keywords: Thyroid carcinomas; Histopathological change; PTC/FTC ratio; Periodicity